Functional and clinical outcome of MIPPO anterolateral plating for proximal tibia fracture both proximal one third and coronal intrarticular fracture - Meena, Dinesh Kumar; Choubisa, Raghvendra; Juneja, Johney; Sharma, Anamendra (International Journal of Research in Orthopaedics, 2021)
Background: The proximal tibial fractures are one of the commonest intraarticular fractures. Generally these injuries fall into two broad categories, high energy fractures and low energy fractures. The tibial plateau fractures are mostly due to high velocity road traffic accidents and fall from height, where fractures result from direct axial compression, usually with a valgus (more common) or varus moment and indirect shear forces. Methods: This is a prospective study and includes operations by MIPPO technique that were undertaken between January 2020 till June 2021 in RNT government hospital; Udaipur. The total number of cases studied were 25 with the youngest being 25 years old and oldest 70 years old. Intraoperative complications were noted. Functional outcome was assessed using Modified Rasmussen’s Criteria. Results: Patients with fracture in our study occurred between the age of 25 to 70 years with maximum incidence involving the productive age group of 21-30 years (90%). Majority of the patients was males- 90%. Conclusions: From the minimally invasive percutaneous plate osteosynthesis of proximal tibial fracture there is an increase in the complexity of proximal tibial fractures with increasing road traffic accident. As most of the patients sustained these fractures belong to physically highly active and productive age group, they need optimal treatment to get back to their previous work capacity and avoid long term complications like osteoarthritis. We treated all fractures in our study with MIPPO technique and found rapid healing by secondary fracture union and hence achieving strong bone union across the fracture site due to inherent benefits of less tissue damage and minimal disturbance of fracture site biology. We operated 20 proximal tibial fractures with MIPPO technique and observed rapid healing and good functional recovery.